PENGARUH KEPERCAYAAN DIRI (SELF CONFIDENCE) BERBASIS KADERISASI IMM TERHADAP PRESTASI BELAJAR MAHASISWA (STUDI KASUS DI PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS MUHAMMADIYAH PAREPARE) - Asrullah Syam; Amri Amri (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2017)
This research has purpose to know and study self confidence based on Kadernisai IMM, learning achievement and self confidence based on Kadernisai IMM on student achievement of Biology Education Study Program Faculty of Teacher Training and Education of Universitas Muhammadiyah Parepare. This research is an associative quantitative research, but researchers do the treatment to collect data by distributing questionnaires, tests, structured interviews. Data collection methods used are Psychological Scale (self-confidence scale) IMM-based cadre and documentation. Research carried out by going through the stages of planning and implementation. Data analysis techniques used two types of analysis that is descriptive statistical analysis and inferential statistical analysis. Based on the results of research and discussion, self confidence based on IMM cadre of students in Biology Education Study Program Force 2014 is in enough category, student learning achievement in Biology Education Study Program Force 2014 is in the category of very satisfying while confidence (self confidence) Based on IMM cadre on the achievement of student learning in Biology Education Study Program Force 2014 Faculty of Teacher Training and Education of Universitas Muhammadiyah Parepare. Contribution of confidence variable (self confidence) based on IMM cadre of 94.1% while the remaining 6.6%.